2016
DOI: 10.1016/j.actamat.2015.12.048
|View full text |Cite
|
Sign up to set email alerts
|

A coupled effect of nuclear and electronic energy loss on ion irradiation damage in lithium niobate

Abstract: Understanding irradiation effects induced by elastic energy loss to atomic nuclei and inelastic energy loss to electrons in a crystal, as well as the coupled effect between them is a scientific challenge. Damage evolution of LiNbO 3 irradiated by 0.9 and 21 MeV Si ions at 300 K has been studied utilizing Rutherford backscattering spectrometry and channeling technique. During the low-energy ion irradiation process, damage accumulation produced due to elastic collisions is described utilizing a disorder accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…Comparing pre-damaged to pristine LiTaO 3 in Figure 5, we note the large increase in disorder in the case of pre-damaged LiTaO 3 . Unambiguously, this highlights the strong interaction between initial disorder and S e , similar to behavior observed in LiNbO 3 [8,9], but with less sensitivity to amorphization. Although possessing many similar structural properties, LiNbO 3 and LiTaO 3 exhibit significant difference in melting temperatures (T m ), curie temperatures (T c ) and band gaps, which may explain the differences in track formation.…”
Section: Mev Si Ion Irradiation In Pre-damaged Crystalsupporting
confidence: 53%
See 1 more Smart Citation
“…Comparing pre-damaged to pristine LiTaO 3 in Figure 5, we note the large increase in disorder in the case of pre-damaged LiTaO 3 . Unambiguously, this highlights the strong interaction between initial disorder and S e , similar to behavior observed in LiNbO 3 [8,9], but with less sensitivity to amorphization. Although possessing many similar structural properties, LiNbO 3 and LiTaO 3 exhibit significant difference in melting temperatures (T m ), curie temperatures (T c ) and band gaps, which may explain the differences in track formation.…”
Section: Mev Si Ion Irradiation In Pre-damaged Crystalsupporting
confidence: 53%
“…Inelastic and elastic processes are generally assumed to be independent and noncorrelated. This concept has been disproved by several studies performed in different ceramics, such as LiNbO 3 [8,9], SiC [6,10,11] and SrTiO 3 [7,12]. Ionization effects and the combination of elastic and inelastic processes in Li-based oxide ceramics, specifically LiTaO 3 , have not been established in the MeV energy regime, and little is understood about the coupled electronic and atomic processes.…”
Section: Introductionmentioning
confidence: 99%
“…Many sequential double ion beam irradiation studies of SiC 1 2 3 , MgO 3 , fluorapatite 4 5 6 and glasses 7 8 have shown that the pre-existing defects induced by the first particle can be annealed by the electronic ionization (LET) due to the second irradiating particle. On the other hand, molecular dynamics and sequential irradiation studies of SrTiO 3 9 10 and LiNbO 3 11 have shown that the pre-existing defects can enhance the ionization induced damage formation, commonly called as synergy. Therefore, depending on the nature of the material, defect recovery as well as synergistic effects can be observed.…”
mentioning
confidence: 99%
“…In the research field of ion-solid interactions and irradiation effects, systematic study of the response of crystal materials to the deposition of irradiation energy to electrons and atomic nuclei has always attracted considerable attention. As a research focus, understanding and clarifying the relevant physical mechanisms is not only fundamental to predicting and evaluating the damage behaviors of materials in natural and man-made radiation environments [5], but it is also key to the applications of ion and electron beam techniques in atomic-level defect manipulation, material modification, and micro/nanofabrication [6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%